3D printing of calcium phosphate scaffolds with controlled release of antibacterial functions for jaw bone repair. (April 2020) - Sun, Huan; Hu, Cheng; Zhou, Changchun; Wu, Lina; Sun, Jianxun; Zhou, Xuedong; Xing, Fei; Long, Cheng; Kong, Qingquan; Liang, Jie; Fan, Yujiang; Zhang, Xingdong
Abstract: Jaw bone repair requires scaffold with bone regeneration, antibacterial function and personalized size. This study proposed 3D printed degradable calcium phosphate scaffolds with antibacterial functions for regeneration of jaw bone. Calcium phosphate powders and berberine were combined to modulate the printing inks. Porous scaffolds were fabricated by direct extrusion 3D printing and cross-linked with sodium alginate in situ. The dimensional size, shape and porosity of scaffolds were precisely customized by 3D printing. Berberine-loaded scaffolds show sustained release of antimicrobial drugs. By adjusting the concentration and cross-linking time of calcium chloride, the cross-linking degree of the scaffold can be adjusted and the drug load of the scaffold can be controlled. The young's modulus of 3DP scaffold was about 1.3 MPa. After freeze-drying, the shrinkage was about 24.4% and less swelling was observed, indicating that the scaffold had sufficient structural stability. In vitro biological test showed that the 3DP scaffold had low cytotoxicity and it was beneficial to MC3T3 cell adhesion and proliferation. 3D printed calcium phosphate scaffolds with controlled-release antibacterial properties is a promising biomaterials for jaw repair. Graphical abstract: Unlabelled Image Highlights: Calcium phosphate powders and berberine were combined to modulate the printing inks. Porous scaffolds were fabricated by direct extrusion 3D printing. Porous scaffolds were cross-linked with sodium alginate in situ. The dimensional size, shape and porosity of scaffolds were precisely customized by 3D printing. Berberine-loaded scaffolds show sustained release of antimicrobial drugs.